(untitled) (Global Journal of Human-Social Science, 2018)
This paper discusses the strategies for enhancing Teacher-Learner communication as used for effective lesson delivery in the classroom in the 21 st century In discussing the subject matter it examined the concept of communication types viz verbal and non-verbal roles strategies the classroom types and features Conclusion was drawn with regard to the need to adapt the applications of ICTS apparatus in the effective delivery of lessons in the classroom especially in the new era of the 21 st century Recommendations were suggested on the need to run a synergy between the teachers students on better ways of acquiring good communication skills for effective teaching to sustain feedback of the national development